Water consumption of an evaporative cooling systemin the midwest - Joseph P. Harner; Smith John (Kansas Agricultural Experiment Station Research Reports, 2009)
Water meters were installed on the evaporative cooling system of a long, low-profile, cross-ventilated dairy in the upper Midwest. The evaporative pad along the west side measured 10 by 350 ft. The water usage per unit surface area of the evaporative pad was 0.29 gallons/hour per square foot of evaporative pad surface area. The total daily water usage per stall averaged 13 gallons with a maximum of 22.7 gallons. Results from this study indicate that peak hourly water usage may be as much as 3 times the average values. The evaporative pad efficiency was 65% between noon and 0800 hours and 79% between midnight and 0400 hours.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Evaporative cooling; Heat stress; Temperature; Water use